A New Subspecies of the Genus Ormyrus (Hymenoptera, Ormyridae) and New Species of the Genus Idiomacromerus (Hymenoptera, Torymidae) from Israel - Zerova, M.D.; Seryogina, L.Ya.; Pavlíček, T.; Nevo, E. (Вестник зоологии, 2002)
Ormyrus gratiosus hermonicus Zerova, subsp. n. (type locality: Mount Hermon) and Idiomacromerus mirabilis Zerova, sp. n. (type locality: Mount Carmel) from northern Israel are described.